POLITENESS STRATEGIES PERFORMED IN PIERS MORGAN AND DONALD TRUMP INTERVIEW - Ela Martisa; Asraf Asraf; La Aso (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
This research aims to describe politeness strategies performed by Piers Morgan and Donald Trump in an interview held on the 25th of January 2018 at the World Economy Forum in Davos, Switzerland. It is used the theory of politeness strategies proposed by Brown and Levinson (1987). This research employs a descriptive qualitative method by taking the transcription of the interview. The data analysis reported that the participants of the interview employed positive and negative politeness strategies to save one another’s faces. The result of the research shows that the participants of the interview attempt to decrease and keep the social distance between them through positive and negative politeness strategies. As a journalist, Piers Morgan tries to handle the conversation to run smoothly. He employs more negative politeness strategies than Donald Trump who has higher social status as the President of the USA. In this event, powerless participants need to be more polite than powerful participants.